The Impact of Skimming and Scanning Technique Toward Students’ Reading Comprehension: Meta–analysis - Fetriani (Edelweiss : Journal Of Innovation In Educational Research, 2025)
This study survey of recent research on Skimming and Scanning Technique Toward Students’ Reading Comprehension. Skimming and scanning techniques can be particularly valuable, as they enable students to efficiently locate relevant information and synthesize content from multiple sources. The present study is a meta–analysis, which synthesized the data of 15 empirical studies. It was designed to explore the impact of skimming and scanning techniques toward students’ reading comprehension, and the implications for instructional strategies in diverse educational settings. The results revealed that: (1) these techniques can significantly enhance students' reading comprehension, promote greater engagement, and cater to diverse learning needs; (2) the integration of skimming and scanning techniques should be prioritized to equip students with the skills necessary for navigating an increasingly complex information landscape